Revealing the mechanism of synergistic antibacterial effect of silver nanoparticles in combination with vancomycin against Enterococcus species by fluorescence microscopy visualization - Válková, Lucie; Hochvaldová, Lucie Suchánková; Mistrík, Martin; Kolář, Milan; Langová, Kateřina; Kolářová, Hana; Štefková, Barbora; Prucek, Robert; Kvítek, Libor; Panáček, Aleš (Journal of materials chemistry. B, 2025)
Silver nanoparticles (Ag NPs) significantly enhance the antibacterial activity of antibiotics and even restore their effect against resistant strains, making them a promising option for overcoming bacterial resistance to antibiotics. However, the exact mechanism of their synergistic effect with antibiotics at the cellular level has not been elucidated. In this work, we synthesised rhodamine-labelled Ag NPs and described, for the first time, the multi-level non-specific mechanism of the synergistic antibacterial effect of fluorescently labelled Ag NPs and a fluorescent vancomycin conjugate against vancomycin-resistant enterococci using high-resolution fluorescence microscopy. The multi-level mechanism of the synergistic effect of Ag NPs and vancomycin is mainly based on the disruption of the strength and integrity of the cell wall, which becomes unstable, loses strength and subsequently disintegrates due to the oxidative stress caused by Ag NPs and the residual effect of vancomycin. In addition, Ag NPs penetrate the bacterial cell and deform the bacterial DNA, which also significantly increases the synergistic antibacterial effect. This work represents an advance in understanding the mechanism of synergistic effect of Ag NPs with antibiotics against resistant bacteria, an important finding for a potential approach to effectively combat the unsolved problem of increasing resistance of pathogenic bacteria to traditional antibiotics.
Keywords: Metal Nanoparticles; antibakteriální látky; Drug Synergism; synergismus léků; Anti-Bacterial Agents; kovové nanočástice; Silver; Microbial Sensitivity Tests; stříbro; vankomycin; mikrobiální testy citlivosti; Enterococcus; Microscopy, Fluorescence; Vancomycin; fluorescenční mikroskopie